2022
DOI: 10.1002/ehf2.14136
|View full text |Cite
|
Sign up to set email alerts
|

Aortic thoracic neuromodulation in heart failure with preserved ejection fraction

Abstract: The inadequacy of medical therapies for heart failure with preserved ejection fraction (HFpEF) is driving the development of device‐based solutions targeting underlying pathophysiologic abnormalities. The maladaptive autonomic imbalance with a reduction in vagal parasympathetic activity and increased sympathetic signalling contributes to the deterioration of cardiac performance, patient fitness, and the increased overall morbidity and mortality. Thoracic aortic vagal afferents mediate parasympathetic signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…39,40 In addition, the vagal aortic afferent nerves, located in the upper part of the thoracic aorta, mediate parasympathetic neuronal transmission to the brain. [39][40][41] Device-based aortic stimulation targets these vagal afferents (mechanoreceptors) in the descending aorta to modulate parasympathetic tone via chronic stimulation. The Endovascular NeuromoDulation Treatment for Heart Failure Patients (ENDO-HF, NCT02633644) feasibility study evaluates the safety and feasibility of the Harmony aortic stimulation system in the treatment of up to 20 patients with HF over 5 years of follow-up.…”
Section: Aortic Vagal Nerve Stimulationmentioning
confidence: 99%
See 3 more Smart Citations
“…39,40 In addition, the vagal aortic afferent nerves, located in the upper part of the thoracic aorta, mediate parasympathetic neuronal transmission to the brain. [39][40][41] Device-based aortic stimulation targets these vagal afferents (mechanoreceptors) in the descending aorta to modulate parasympathetic tone via chronic stimulation. The Endovascular NeuromoDulation Treatment for Heart Failure Patients (ENDO-HF, NCT02633644) feasibility study evaluates the safety and feasibility of the Harmony aortic stimulation system in the treatment of up to 20 patients with HF over 5 years of follow-up.…”
Section: Aortic Vagal Nerve Stimulationmentioning
confidence: 99%
“…Long-term stimulation aims at decreasing sympathetic tone and increasing parasympathetic tone, resulting in lowering of heart rate and LV afterload. 41 However, according to the United States Clinical Trials Registry, the ENDO-HF trial has been terminated. 42…”
Section: Aortic Vagal Nerve Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…It comprises an implantable unit, delivery catheter, patient wearable unit, and programming unit. In this study, chronic stimulation of aortic vagal afferents using this system has been shown to improve left atrial remodeling and function, as well as left ventricular performance, highlighting the potential of neuromodulation therapy as an effective treatment for HFpEF [ 51 ].…”
Section: Pharmacological and Non-pharmacological Treatments Of Hfpefmentioning
confidence: 99%